(untitled) - Robinson, Chase F (Cambridge, 2000)
Chase Robinson's book takes full account of the latest research, interweaving history and historiography to interpret the political, social, and economic transformations in the Mesopotamian region after the Islamic conquests. Using Arabic and Syriac sources, the author focuses on the Muslim and Christian élites, demonstrating that significant social change took place only at the end of the seventh century. This is a sophisticated study at the cutting-edge of a burgeoning field in Islamic studies.
Keywords: Khoa học xã hội,Mosul (Iraq),Elite (social sciences),Mosul (Iraq); Đế chế Hồi giáo,Lịch sử,Islamic empire,History